2016
DOI: 10.1007/s12374-016-0539-9
|View full text |Cite
|
Sign up to set email alerts
|

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis

Abstract: Zinc nger proteins (ZFPs) play important roles in plant responses to biotic and abiotic stresses. Through microarray analysis, an Oryza sativa L. multi-stress-responsive gene, OsMSR15, was identied and subsequently cloned from rice Pei'ai 64S (Oryza sativa L.). Expression of OsMSR15 was strongly up-regulated by cold, drought and heat stresses in different tissues at different developmental stages of rice. OsMSR15 contains two C2H2-type zinc nger motifs, a nuclear localization signal (B box), a Leu-rich domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Transgenic plants overexpressing OsMSR15 show hypersensitivity to exogenous ABA. Transgenic plants also showed increased expressions of a number of stressresponsive genes, including RD29A and DREB1A under drought stress, which suggested that OsMSR15 may play important roles in response to drought stress both in ABAdependent and -independent pathways (Zhang et al, 2016c). In the ZAT18 overexpression lines, RNA-seq analysis revealed the enrichment of pathways, such as hormone metabolism, stress response, and signaling pathways; stress-related genes, such as COR47, ERD7, LEA6, RAS1, and hormone-signaling-transduction-related genes, such as JAZ7 and PYL5, appear to be the downstream target genes of ZAT18 (Yin et al, 2017).…”
Section: Roles In Drought Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgenic plants overexpressing OsMSR15 show hypersensitivity to exogenous ABA. Transgenic plants also showed increased expressions of a number of stressresponsive genes, including RD29A and DREB1A under drought stress, which suggested that OsMSR15 may play important roles in response to drought stress both in ABAdependent and -independent pathways (Zhang et al, 2016c). In the ZAT18 overexpression lines, RNA-seq analysis revealed the enrichment of pathways, such as hormone metabolism, stress response, and signaling pathways; stress-related genes, such as COR47, ERD7, LEA6, RAS1, and hormone-signaling-transduction-related genes, such as JAZ7 and PYL5, appear to be the downstream target genes of ZAT18 (Yin et al, 2017).…”
Section: Roles In Drought Stressmentioning
confidence: 99%
“…C2H2-type zinc finger proteins with EAR motifs play important roles in regulating abiotic-stress-related gene expression under conditions such as salt, drought, and low temperature (Han and Fu, 2019). The DLNL sequence (DLNbox) at the C-terminus of STZ, with trans-activation activity, functions in the transcriptional activation of DREB1A under salt stress (Sakamoto et al, 2004;Kazan, 2006;Zhang et al, 2016c;Li et al, 2018), while the DLN-box is not the only domain that determines the transcriptional inhibitory activity of C2H2 zinc finger proteins (Huang et al, 2009a).…”
Section: Transcriptional Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the analysis and molecular characterization of the regulatory network of stress-related genes in rice, we carried out a microarray-based study of global genome expression profiles of a male-sterile indica cultivar, Pei’ai 64 S (PA64S), subjected to cold, heat or drought stresses using Affymetrix GeneChip ® arrays22232425. The analysis of microarray data showed that many genes were up- and down-regulated by different stresses in the rice genome (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…OsHBP1b belongs to bZIP family of transcription factors that activates ROS detoxification system and increases the content of protective molecules (i.e., soluble sugars and proline) under stressed conditions. A putative H 2 O 2 and ABA-responsive C 2 H 2 -type zinc finger protein OsMSR15 (Oryza sativa multi-stress-responsive protein) has been also identified in rice that enhances drought and oxidative stress tolerance via elevating antioxidant activities and ABA sensitivity (Zhang et al 2016). The biological role of another plant-specific protein-GRAS protein family (Gibberellic Acid Insensitive GAI, Repressor of GAI, and SCARECROW, acting as bZIP transcription factors) in conferring abiotic stress tolerance in rice has been also explicated recently; enhanced expression of OsGRAS23 in transgenic rice resulted in high drought as well oxidative stress resilience via reducing H 2 O 2 accumulation (Xu et al 2015).…”
Section: Basic Leucine Zipper (Bzip)mentioning
confidence: 99%